Réponses

2013-03-16T18:05:23+01:00

f(x) =  (4(x+2))-1

= (4x+8)-1

= 4x+7

 

f(1/2) = 4 x 1/2 - 7 = 2 - 7 = -5

 

f(x) = 0

4x+7=0

4x=-7

x=-7/4

 

f(x) = 3

4x+7=3

4x=-4

x=-4/4

x=-1

 

2013-03-16T18:28:57+01:00

f(x) = (4(x+2))-1

 

Si x = 1/2, alors :

f(1/2) = (4(1/2 + 2))-1

          = 4*1/2 + 4*2 - 1

          = 2 + 8 - 1

          = 9

 

Si x = -2 + v2, alors

f(-2 + V2) = (4(-2 + V2 + 2))-1 

                 = - 8 + 4V2 + 8 - 1

                 = - 1 + 4V2

 

Si  f(x) = 0, alors :

(4(x + 2))-1 = 0

4x + 8 - 1 = 0

4x + 7 - 7 = 0 - 7

4x / 4 = -7 / 4

x = - 7/4

 

Si f(x) = 3, alors :

(4(x+2))-1 = 3

4x + 8 - 1 = 3

4x + 7 - 7 = 3 - 7

4x / 4 = - 4/4

x = - 1